2001
DOI: 10.1177/172460080101600407
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone Receptors in Colorectal Cancer and Surrounding Mucosa

Abstract: In this prospective study we have quantified by means of ELISA-methods the cytosolic content of estrogen (ER) and progesterone receptors (PgR) in tumoral tissue and paired normal mucosa from 163 patients with resectable colorectal cancer. Survival analysis was performed in a subgroup of 120 patients and the mean follow-up period was 24.9 months. The cutoff for ER and PgR levels was set at 1 fmol/mg protein. On the basis of this cutoff 20.9% of the cancers were ER positive and 25.8% were PgR positive; normal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Recent re-analysis of world wide data on the relationship between hormone replacement therapy and breast cancer showed that the risk of this cancer may be increased in women who are taking estrogen [123] . Estrogen receptors are reported to be present in colorectal tissue and colorectal adenocarcinoma and ER-β is found to be the predominate receptor expressed in colonic tissue [124][125][126][127][128][129][130] (Table 1).…”
Section: Surrogate End Point In Colon Cancermentioning
confidence: 99%
“…Recent re-analysis of world wide data on the relationship between hormone replacement therapy and breast cancer showed that the risk of this cancer may be increased in women who are taking estrogen [123] . Estrogen receptors are reported to be present in colorectal tissue and colorectal adenocarcinoma and ER-β is found to be the predominate receptor expressed in colonic tissue [124][125][126][127][128][129][130] (Table 1).…”
Section: Surrogate End Point In Colon Cancermentioning
confidence: 99%
“…16 Progesterone and oestradiol receptors have been found in normal colonic tissue. 17 Multiple studies failed to show a clear or consistent effect of female sex hormones on gastric emptying, small bowel transit and colonic transit with either longer orocecal transit time in the luteal phases compared with the follicular phases 9,11,12 or no significant variation with the phase of the menstrual cycle in whole gut, 18,19 orocecal, 19 or colonic transit. 8 Our aim was to clarify the effects on colonic transit of doses of progesterone and oestradiol that intended to mimic the levels occurring in the luteal phase of the menstrual cycle and the withdrawal of sex hormones, as occurs immediately prior to menstruation.…”
Section: Introductionmentioning
confidence: 99%
“…At the tissue level, sex hormones inhibit muscle contractility in a variety of sites, including uterus, gall bladder, 14 lower oesophageal sphincter, 15 and colon 16 . Progesterone and oestradiol receptors have been found in normal colonic tissue 17 …”
Section: Introductionmentioning
confidence: 99%
“…Because of the similarities in BMI associations for women exposed to estrogen and for men, it has been hypothesized that androgen, as well as estrogen, might be related to colon cancer risk. Both estrogen and androgen receptors are present in colorectal tissue (7)(8)(9)(10)(11)(12). Most of the actions of estrogens and androgens seem to be exerted through the respective receptors (13,14), suggesting that the estrogen receptor and androgen receptor may be important in regulating colorectal cancer risk associated with these hormones.…”
Section: Introductionmentioning
confidence: 99%